Analisis Dampak Lalu Lintas Terhadap Inventarisasi Jalan Akibat Operasi Terminal LPG Tuban - Soimun, Ahmad; Amijaya, Jimi; Baskara, Wahyu Padma; Krisnayanthi, Ni Komang Novia (Universitas Kristen Maranatha, 2024)
Refrigerated LPG Terminal is a facility that handles liquefied gas as a raw material, ensuring a reliable supply of LPG for the community. Located in Remen Village, Jenu Subdistrict, Tuban Regency. The intensity of land use changes in an area will correspond to changes in the transportation system in that area. The construction of an LPG terminal will undoubtedly have transportation-related impacts in the area. Therefore, efforts are needed to address these issues by formulating traffic engineering management that is tailored to the actual conditions. The method used involves observational surveys such as Trips Attraction Survey and Origin Survey, which focus on inventorying the roads around the construction area. The impact analysis method of development using MKJI is employed. The analysis of the impact of the development of PT. Pertamina LPG terminal shows that from the existing condition before the development, during the construction phase, and at the early operation stage, it does not significantly affect the capacity of the existing roads in the area. In the forecast period of the next 5 years, there will be an increase in the road capacity value of DJ during the morning peak from 0.248 to 0.334. Regarding the level of service (LOS), it remains at level B for the existing period, construction phase, and early operational stage. By analyzing using forecasting methods, alternatives that can be planned include traffic control systems, understanding the road network system around the area, providing public transportation, installing traffic signs, providing parking facilities, and minimizing roadside parking.